Evaluation of the Methods of Using of GnRH to Induce Ovulation in the Purebred Arabian Mares in Syria (Journal of Hama University, 2022)
Twenty-eight purebred Arabian Mares, 5-12 years old, were used in this present study to evaluate whether the administration of the GnRH to induce ovulation for determine the preferred time of mating and increase fertility rate. Mares were divided randomly into four groups (7 mares per group). In the experimental group (G1), a total dose of GnRH (40 µg) were injected Subcutaneous (SC) of the labia of the vulva when the dominant follicle reached a diameter of (42±2mm). In the experimental group (G2), a total dose of GnRH (40 µg) were injected Intramuscular (IM) when the dominant follicle reached a diameter of (42±2mm). In the experimental group (G3), a total dose of GnRH (40 µg) were injected intravenous (IV) when the dominant follicle reached a diameter of (42±2mm). In the control group (G4), 10 ml physiological solution was injected when the dominant follicle reached a diameter of (42±2mm). The mares were then examined every 12 hours to determine the ovulation time. Mares were mated only once 24 hours after injection of GnRH or physiological solution. The Pregnancy was then examined by ultrasound in 18, 30 and 90 days. Results showed that there were significant differences (P0.05) between experimental G1 and G2 comparatively with experimental G3 and control group (85.71%, 85.71%, 71.43% and 57.12%) respectively. These results indicate that only a single dose (40 µg of GnRH) subcutaneous of the labia of the vulva or intramuscular administration, when follicles reached a diameter (42±2mm), was effectives to induce time of ovulation to increase the fertility and pregnancy rate in the Purebred Arabian Mares in Syria.